Etiological profile of short stature in children and adolescents - Rajesh Rajput (Wolters Kluwer Medknow Publications, 2021)
Context: The delayed growth of a child is a major cause of concern for the parents. There is a multitude of etiological factors which must be considered in relation to this common aspect of healthcare. Aim: The study was done to evaluate the etiological profile of short stature in children and adolescents. Settings and Design: The cross-sectional study was conducted for 12 months including 111 cases of short stature (out of the 1,058 cases screened), at the endocrinology outpatient department (OPD) of a tertiary care institute in Haryana. Subjects and Methods: As per the inclusion criteria, cases with age <18 years were enrolled. The examination and anthropometric measurements were performed in the presence of parents/guardians. Results: Out of the 1,058 cases screened; 111 cases of short stature were recruited as per the inclusion and exclusion criteria. The prevalence was about 10.49% of the total population. The mean age of the sample was 12.34 ± 3.19 years. The endocrine causes were the most common followed by normal variants of growth and delay, chronic systemic illness, and nutritional and skeletal causes. Among the endocrine causes, hypothyroidism was the most common followed by growth hormone deficiency and type 1 diabetes mellitus (T1DM). Conclusions: The mean chronological age of 12.34 ± 3.19 years suggests the delayed detection of short stature in the population. This highlights the importance of educating parents so that timely therapeutic intervention can be done to achieve the potential height.